Implementasi Aspek Palemahan Pada Awig-Awig Subak Anggabaya - Anak Agung Putu Sugiantiningsih (Visi Sosial Humaniora, 2023)
Subak is a system of farmer organizations in managing irrigation water for its members who manage agricultural land. Subak is also often discussed as a big museum, where people can learn about the application of a philosophy, whose name is Tri Hita Karana (THK). Awig-awig subak is a subak guideline for welfare and is managed according to the designation of a protected world cultural heritage. With the existence of awig-awig subak, it can maintain its sustainability, and greetings from awig-awig, subak can also be implemented in 3 aspects of Tri Hita Karana. Therefore, it can be taken from the formulation of the problem, namely how is the implementation of the Pawongan aspect in Awig-Awig Subak Anggabaya? The method of collecting data by way of observation, interviews, and documentation. This research will be analyzed using a qualitative descriptive analysis method, obtained from research results in the form of qualitative and quantitative data will be presented in the form of narratives and tables arranged systematically and efficiently. The results showed that the implementation of the Pawongan aspect in Awig-awig Subak Aggbaya had been carried out well although there were several awig-awig that were not carried out or modified but the provisions were the same but the implementation was different.